Análise das interações professor-aluno com Paralisia Cerebral no contexto da sala de aula regular - Lima, Vivian Caroline de (2011)
The current literature in the area of Special Education that deals with the process of inclusion of a person with special needs in social spheres has been shown that such a process is still rooted only in the theories and laws that proclaim it, that is, the theories and daily actions are strongly disconnected. Nevertheless, the school is still considered a privileged social environment where the cultural and social identities and the complete formation of the citizen are built up through actions and the interaction between the subjects. Considering the importance of the relationship between the teacher and the student in the process of building up an education that aims for the complete development of the students, the aim of this study was to analyze how the interactions between the teacher and the student with Cerebral Palsy that occurred in both the teaching and learning process have been constituted in the context of the mainstream classroom, regarding the obstacles when it comes to pedagogical inclusive practices directed to this student. The participants in this research were two teachers of two mainstream elementary schools of a city located at the central region of São Paulo State and two female students with Cerebral Palsy who are regularly enrolled. The methodology was guided through weekly observation which lasted four months, based on a structured schedule, registration of collected information through filming and writing of a diary, and analysis of collected data. The results showed differences in relation to the number of interactive episodes that occurred in each school, as well as to the content and the situation in which they occurred, and to the kind of action taken by the participants. In conclusion, the research showed that the interaction teacher-student may contribute in the positive way to the learning of students with Cerebral Palsy from the viewpoint of the inclusive education, besides the problems pointed in the context of both schools.